Pemanfaatan Aplikasi Kahoot sebagai Media dalam Pembelajaran PAI di SDN 6 Syamtalira Bayu - Cut Intan Nurbalqis; Yusnaini Yusnaini (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study addresses the low level of student engagement and participation in Islamic Religious Education (PAI), which is often dominated by lecture-based instruction. The research aims to examine how the Kahoot application can be utilized as an interactive learning media to improve students’ engagement and learning experiences. A qualitative descriptive approach was employed, involving fourth-grade students at SD Negeri 6 Syamtalira Bayu as research participants. Data were collected through questionnaires and semi-structured interviews to capture students’ responses and learning behaviors during the implementation of Kahoot. The findings reveal that the use of Kahoot contributes positively to the learning process. Most students reported increased interest, active participation, and higher motivation during lessons. In addition, the application encouraged students to prepare before class, such as reading learning materials and seeking additional references. Kahoot also created a more interactive and enjoyable classroom atmosphere through game-based quizzes, which helped students better understand PAI concepts. Despite minor challenges related to device availability and internet access, Kahoot proved to be an effective and innovative alternative for enhancing both the learning process and student outcomes in PAI.